Perancangan Aplikasi Pemetaan Fasiltas Kesehatan Di Kabupaten Lebong Berbasis Android - M Fakhrur Riozi; Agung Kharisma Hidayah; Anisya Sonita; Eka Sahputra (UNIVED Press, 2024)
Health facilities are places where health efforts are carried out. In this research, several problems were found regarding health facility information, such as the official Lebong district website only providing some information on health facilities such as hospitals, health centers, pharmacies. Not all health facility locations are known to the public, whether they come from Lebong Regency or immigrants from Lebong Regency. If you use the Google Maps application, there are still health facility locations that are not registered, so this application can complete data that has not been registered in the Google Maps application. so that the public can know better and make it easier to disburse the location of health facilities. This system was created using the prototyping method, system development process, system implementation and finalization. This application was developed with Kodular. Apart from that, the framework used uses DFD and UI UX Design as examples of application design.